Food Hygiene and Applied Food Microbiology in an Anthropological Cross Cultural Perspective - Zaccheo, Aleardo; Palmaccio, Eleonora; Venable, Morgan; Locarnini-Sciaroni, Isabella; Parisi, Salvatore (Springer International Publishing : Imprint: Springer, 2017)
The book demonstrates that food safety is a multidisciplinary scientific discipline that is specifically designed to prevent foodborne illness to consumers. It is generally assumed to be an axiom by both nonprofessionals and professionals alike, that the most developed countries, through their intricate and complex standards, formal trainings and inspections, are always capable of providing much safer food items and beverages to consumers as opposed to the lesser developed countries and regions of the world. Clearly, the available data regarding the morbidity and the mortality in different areas of the world confirms that in developing countries, the prevalence and the incidence of< presumptive foodborne illness is much greater. However, other factors need to be taken into consideration in this overall picture: First of all, one of the key issues in developing countries appears to be the availability of safe drinking water, a key element in any food safety strategy. Second, the availability of healthcare facilities, care providers, and medicines in different parts of the world makes the consequences of foodborne illness much more important and life threatening in lesser developed countries than in most developed countries. It would be therefore ethnocentric and rather simplistic to state that the margin of improvement in food safety is only directly proportional to the level of development of the society or to the level of complexity of any given national or international standard. Besides standards and regulations, humans as a whole have evolved and adapted different strategies to provide and to ensure food and water safety according to their cultural and historical backgrounds. Our goal is to discuss and to compare these strategies in a cross-cultural and technical approach, according to the realities of different socio-economic, ethnical and social heritages.- Resumé vydavatel
Keywords: potravinářská mikrobiologie; bezpečnost potravin; hygiena potravin; veřejné zdraví; food microbiology; food safety; food hygiene; public health; elektronické knihy; sborníky; electronic books; papers of several authors